PENGARUH PENAMBAHAN PROBIOTIK TERHADAP PERFORMA PERTUMBUHAN DAN KESEHATAN BENIH IKAN GABUS (Channa striata) DI SISTEM BUDIKDAMBER - Sudrajat, Rizky Ahmad; Grandiosa, Roffi; Haetami, Kiki; Zidni, Irfan (Jurnal Perikanan Unram, 2025)
This study aims to analyze the effect of the addition and optimal dose of probiotics on the growth performance and health of snakehead fish (channa striata) seeds in the budikdamber system. The budikdamber system is an innovation in fisheries cultivation in limited land that is easy to apply at home by the community at an affordable cost. The study was conducted using a completely randomized design (CRD) consisting of 4 treatments of probiotic doses and a control without probiotics, with each treatment repeated three times. The treatments used were (A) without the addition of probiotics (control), (B) the addition of probiotics as much as 0.6 ml/L of water, (C) the addition of probiotics as much as 0.8 ml/L of water, (D) the addition of probiotics as much as 1.0 ml/L of water, and (E) the addition of probiotics as much as 1.2 ml/L of water which were maintained for 40 days. The test fish used were 5-6 cm in size and weighed 1-2 grams. The container used was a plastic bucket with a volume of 80 liters with a water volume of 70 liters where the snakehead fish were placed with a stocking density according to the treatment. The amount of feed given was 5% of the fish biomass. The results obtained during the study showed that treatment C with the addition of probiotics as much as 0.8 ml/L of water produced the highest absolute length growth of 2.71±0.05 cm, the highest absolute weight growth of 2.87±0.27 grams, a specific growth rate of 1.69±0.02%, survival of 89±0.03%, the number of erythrocytes 1,356,800±0.02 and the number of leukocytes 120,617±0.07.